Yakity Yak - Benita Sen (Bharat Pratham Book, 2023)
What do you name a talkative young yak? Yakity Yak, of course. Yakity lives with his parents and grandparents high up in the mountains. He is an unusual yak that is talkative and makes friends with the grass, the flowers, the birds, the clouds and the wind. One cloudy day, Yakity finds himself alone and in danger. Or is he alone? Find out more in this book.
Keywords: IR - I -- IR - I